A Panic-Prone Pack? The Behavior of Emerging Market Mutual Funds - Eduardo R. Borensztein; R. Gaston Gelos (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper explores the behavior of emerging market mutual funds using anovel database covering the holdings of individual funds over the periodJanuary 1996 to March 1999. An examination of individual crises shows that,on average, funds withdrew money one month prior to the events. Thedegree of herding among funds is statistically significant, but moderate.Herding is more widespread among open-ended funds than among closed-endfunds, but not more prevalent during crises than during tranquil times.Funds tend to follow momentum strategies, selling past losers and buyingpast winners, but their overall behavior is more complex than oftensuggested.
Keywords: 330; mutual funds; contagion; emerging markets; foreign portfolioinvestment; herding; financial crises.